2007
DOI: 10.1007/s10096-006-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of vancomycin-resistant enteroccoci and spread of a single clone in a university hospital in northwestern Turkey

Abstract: Reported here is the first isolation of vancomycin-resistant Enterococcus (VRE) at a hospital in northwestern Turkey and a description of the ensuing outbreak investigation. The first isolate was obtained from a wound culture of a patient in an intensive care unit. Thereafter, a total of 205 rectal swabs, 67 skin swabs and 123 environmental samples were screened, revealing five more VRE isolates. All isolates showed similar antibiotic resistance patterns, except for two that differed regarding gentamicin resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…3). The results of our clinical isolate genotypes have been found to be similar to the previous studies (generally the most clinical isolates carried vanA genes) performed in Turkey [24,25] . However, different studies showed variable results concerning the detection rates of vanA and vanB genes in Middle East Countries such as; in Kuwait hospitals, all VRE strains carried the vanA genotype and vanB gene was not detected in any of the isolates [26] .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…3). The results of our clinical isolate genotypes have been found to be similar to the previous studies (generally the most clinical isolates carried vanA genes) performed in Turkey [24,25] . However, different studies showed variable results concerning the detection rates of vanA and vanB genes in Middle East Countries such as; in Kuwait hospitals, all VRE strains carried the vanA genotype and vanB gene was not detected in any of the isolates [26] .…”
Section: Discussionsupporting
confidence: 78%
“…While VRE infections acquired in several research hospitals in Turkey have been reported since 1999, the role and mechanism of the reservoirs in the spread of glycopeptide resistance was not explicit in our country, either. Few studies have been performed on vancomycin resistance and genetic diversity of enterococci clinical isolates in Turkey as well as Middle East Countries [10,24,29] .…”
Section: Discussionmentioning
confidence: 99%
“…After that time, VRE was reported in many hospitals in our country [25][26][27][28]. Fifteen Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…İndeks olguda VRE saptandıktan sonra indeks olgunun rektal sürüntüsünde ve aynı odadaki diğer hastaların rektal sürüntü örneklerinde de VRE saptanması, dışkı kaynaklı kolonizasyonun YBÜ'lerde salgın gelişi-mine zemin hazırlaması bakımından dikkat çekicidir. VRE kaynakları; kolonize veya infekte hastalarla kontamine yüzey ve cihazlardır [18] . [20] .…”
Section: Discussionunclassified